Hubungan Pemberian ASI Eksklusif, Kelengkapan Imunisasi Dasar dan Penyakit Infeksi pada Balita Usia 1-5 Tahun dengan Kejadian Wasting Di Kabupaten Tuban - Filia Alia Rahma; Miftahul Munir; Lilia Faridatul Fauziah (INSOLOGI: Jurnal Sains dan Teknologi, 2024)
Wasting is a malnutrition condition where the toddler's weight does not match the height or z-score value of < - 2SD. One of the direct factors that affect the nutritional status of toddlers or the occurrence of wasting is a history of exclusive breastfeeding, completeness of basic immunizations and infectious diseases. This study aims to analyze the relationship between exclusive breastfeeding, completeness of basic immunization, and infectious diseases with the incidence of wasting in toddlers aged 1-5 years in Tuban Regency. This type of research is cross sectional. The population in this study of all wasting toddlers in Tuban Regency in 2022 was 6,240, and a sample of 400 wasting toddlers from 10 health centers with the highest wasting prevalence in Tuban Regency. The sampling technique used is cluster random sampling, a collection method using secondary data from each puskesmas. The results of the study conducted after being analyzed using SPSS 26 for windows with the spearman test obtained (p < 0.05) then H1 was accepted. For exclusive breastfeeding history (p = 0.000), baseline immunization history (p = 0.000) and infectious disease history (p = 0.000).